Monitoring treatment response and disease progression in myeloma with circulating cell‐free DNA. (10th November 2020) - Deshpande, Shayu; Tytarenko, Ruslana G.; Wang, Yan; Boyle, Eileen M.; Ashby, Cody; Schinke, Carolina D.; Thanendrarajan, Sharmilan; Zangari, Maurizio; Zhan, Fenghuang; Davies, Faith E.; Morgan, Gareth J.; van Rhee, Frits; et al.
Abstract: Circulating cell‐free DNA (cfDNA) has the potential to capture spatial genetic heterogeneity in myeloma (MM) patients. We assessed whether cfDNA levels vary according to risk status defined by the 70 gene expression profile (GEP70). cfDNA levels in 77 patients were significantly higher in the GEP70 high‐risk (HR) group compared to the low‐risk (LR) group and correlated weakly with clinical markers including lactate dehydrogenase, β2 ‐microglobulin, and ISS. Patients with high cfDNA levels were associated with a worse PFS (hazard ratio 6.4; 95% CI of ratio 1.9‐22) and OS (hazard ratio 4.4; 95% CI of ratio 1.2‐15.7). Circulating tumor DNA (ctDNA) was elevated in the HR group and ctDNA correlated strongly with GEP70 risk score (Spearman r = .69, P = .0027). cfDNA concentrations were significantly elevated between days 3‐5 after chemotherapy before falling back to baseline levels. ctDNA in two patients showed a similar spike in levels between days 3 and 5 after chemotherapy with a concomitant increase in allele fraction of KRAS mutations. We assessed cfDNA levels in 25 patients with smoldering myeloma with serial samples and showed increased allele fraction of mutated KRAS at progression in cfDNA. Our study shows that cfDNA is a dynamic tool to capture genetic events in myeloma. Abstract : Monitoring treatment response and disease progression in myeloma with cfDNA